Pengaruh Kecepatan Aliran Udara terhadap Dew Point Effectiveness pada Sistem Pendinginan Maisotsenko-Inderect Evaporative Cooling Non-Venturi dengan Aliran Udara Horizontal Parallel Flow - Tajri, Moch. Nurul; Wijaksana, Hendra; Astawa, Ketut (Teknik Desain Mekanika, 2024)
Abstract The study was conducted to determine the effectiveness of the dew point of the Maisotsenko system cooling device in the variation of parallel flow direction and air flow velocity. The test parameters of this cooling device are the inlet air temperature on the side of the primary air duct, secondary duct, product air temperature on the side of the primary air duct and at the wet duct temperature. This study was conducted to test the Maisotsenko system in a variation of parallel flow direction and speed of 5 m/s, 7 m/s, and 9 m/s. Testing was carried out in a span of 30 minutes and data collection every 5 minutes. The test results obtained the highest temperature reduction at a speed variation of 5 m/s which can reduce the temperature to 2.55oC. Based on the data, the performance of this tool is highly dependent on the air mass flow rate and the result of temperature reduction. Keywords: Maisotsenko cycle, evaporative cooler, parallel flow, Dry bulb temperature, Air flow rate.